Seasonal Impact of Water Parameters Variation on Signal Propagation in Underwater Communication Systems - Adeagbo, Funmilola; Lasisi, Hammed; Aderinkola, Fatimat; Asafa, Mubarak; Alawode, Kehinde; Awofolaju, Tolulope; Olawuyi, Abdulsemiu (Journal of Science and Technology, 2025)
The study explores how environmental variations affect signal propagation in freshwater bodies, focusing on five key sites: Niger River, Asejire Dam, Ede Dam, Osun River, and Eti-Osa River. Employing laboratory-based quantitative analysis, parameters such as temperature, salinity, pH, turbidity, and total dissolved solids (TDS) were measured using standard instruments. Distinct seasonal trends emerged—temperature increased by an average of 8°C in the dry season, while turbidity and TDS rose notably during the rainy period, ranging from 30–150 NTU and 25–80 mg/L in the dry season to 41–200 NTU and 30–120 mg/L in the rainy season. These variations directly influenced acoustic signal performance. The data revealed that higher temperatures improve signal velocity and reduce attenuation, whereas increased turbidity, TDS, and salinity contribute to greater scattering and absorption losses. The novelty of this work lies in its integrated assessment of multi-parameter water quality influences on underwater signal transmission, emphasizing the dual-season comparative approach within tropical freshwater systems. Unlike prior studies that generalized oceanic models, this research contextualizes findings within inland aquatic environments relevant to Nigeria. The study contributes to the existing body of knowledge by quantitatively linking environmental conditions with communication efficiency, establishing that signal reliability in Underwater Communication Systems (UWCS) is seasonally dependent. In conclusion, the results underscore the necessity of adaptive communication models that account for local hydrological dynamics to minimize signal degradation and optimize transmission efficiency across varying aquatic conditions.